Փիլոնի երկերի քրիստոնեական ընկալումը Ալեքսանդրիայում - Աննևիս Վան Դեն Հուք (Մատենադարան)
The Philonic corpus owes its preservation to the Christian tradition of Alexandria; its first appearance is in the works of Clement, and its extension occurs via Origen in Caesarea. The link with Philo at least for Clement was no longer with a living Jewish tradition but with a literary heritage. Thanks to Origen who moved from Alexandria to Caesarea, Philo’s writings ended up in the episcopal library of that city and form the basis of the text of Philo’s works as they have been transmitted to us. One might never have known the many works of Philo were it not for the Christian Alexandrian tradition. Филоновский корпус сохранился благодаря александрийской христианской традиции. Впервые он обнаруживает себя в трудах Климента, связь которого с Филоном больше не осуществлялась через живую еврейскую традицию, но только через литературное наследие. Благодаря Оригену, который переселился из Александрии в Палестинскую Кесарию, труды Филона оказались в епископальной библиотеке этого города и составляют основу дошедших до нас филоновских текстов. Произведения Филона могли бы остаться неизвестными, если бы не христианская традиция Александрии.
Keywords: Փիլիսոփայություն